Enhancing fertilizer-use-efficiency through fertilizer microdosing as climate-smart practices among crop farmers in North Central, Nigeria - Kolapo, Adetomiwa; Oluwatayo, Isaac Busayo; Ayojimi, Wale; Eniola, Awe Toluwalase; Sieber, Stefan (Frontiers in Sustainable Food Systems, 2025)
The impact of climate change, soil fertility depletion, and land degradation has necessitated the continuous use of fertilizer to enhance crop productivity. However, the high cost of fertilizer, coupled with improper use of fertilizer leading to environmental issues, has encouraged efficient use of fertilizer. This study draws on farm-level data to assess the link between the implementation of fertilizer microdosing technology and fertilizer use efficiency among cereal crop farmers in North Central, Nigeria, due to its agroecological importance, high cereal production, and vulnerability to climate change. We used the Heckman two-stage model to explore the adoption and intensity of adoption since it presents a more precise estimation by effectively addressing the endogeneity arising from latent sample selection biases. We examined the mechanism of the effect of the adoption of fertilizer microdosing technology on fertilizer use efficiency using a 2SLS instrumental variable regression to control for unobserved variables. This study found that adoption of fertilizer microdosing technology is gender-sensitive; thus, its application is more common among male farmers. The results show that there is a positive relationship between the adoption of fertilizer microdosing technology and fertilizer use efficiency. The estimated elasticities of fertilizer microdosing technology adoption for maize, sorghum, millet, and maize-sorghum are similar, and the average elasticity of fertilizer microdosing technology adoption is around 0.6. Statistically, a 1% increase in fertilizer microdosing technology adoption is associated with a 0.6% increase in fertilizer use efficiency. These results suggest massive promotion of this technology for use among farmers since it can help reduce fertilizer wastage and ensure a climate-smart practice.